Executive Bonus Plans Accounting Trade-offs: The Case of the Oil and Gas Industry, 1985-86. - Chen, Kevin C.W.; Lee, Chi-Wen Jevons (The Accounting Review, 1995)
Focuses on executive bonus plans and accounting trade-offs in the oil and gas industry during the years 1985-86. Executive bonuses of firms switching to the successful efforts method; Firms that opted for write-down method.